Linkages and imports of Malaysia, 1978-1987 : An input-output approach - Abdul Rashid, Zakariah; Soon, Jan Jan (Universiti Utara Malaysia, 2002)
This article examines the inter-sectoral linkages and imports of Malaysia using the input-output approach. The method employed here will be similar to the work of Achaya and Hazari (1973), where they differentiated between total and domestic linkages. A hypothesis is put forward stating that there will below rank correlation between the total and domestic linkages if the import requirements are relatively high. The results of the analyses suggest a distinct characteristic between the industries generating backward and forward linkages respectively. This study found that there is a high correlation between the total and net forward linkage, suggesting the low import requirements for those industries generating forward linkage. These are in contrast with the results found for those industries generating backward linkage, where the correlation between the total and net backward linkage is lower. This suggests that the import requirements for those indutries generating backward linkage are higher than those industries generating forward linkage.